English As An Instrument of Economic Growth: A Systematic Literature Review - Pratiwi, Rani Julia; Siti Nur Khoiriyah; Konsultindo, Christian Tjatur Budi; Ananda Sriphol; Danardana Murwani; Ludi Wishnu Wardana; Andy Prasetyo Wati (International Journal of Technology and Education Research, 2025)
This study aims to examine the role of English as an instrument in economic growth in Indonesia through a Systematic Literature Review (SLR) approach. The literature selection process followed the PRISMA flow to ensure transparency and validity, and was supported by bibliometric analysis and visualization using VOSviewer software. The literature analyzed came from Google Scholar and Web of Science published between 2019-2025, with keywords focusing on the relationship between English language acquisition and economic growth. From the selection of the initial 100 articles, 9 relevant articles were obtained for further analysis. The results show that English proficiency contributes to four main aspects of economic growth, namely: (1) as a source of individual income through private courses, (2) as an essential skill in entrepreneurship and global business, (3) as a branding tool in the tourism sector, and (4) as a medium of communication with foreign investors. These findings reinforce the human capital theory that places language acquisition as a strategic asset for national economic competitiveness. This study concludes that English is an important instrument in supporting Indonesia's economic growth in the era of globalization.